Development of a method for correcting the placement of the region of interest - Laktionov, Oleksandr; Shefer, Oleksandr; Kyslytsia, Svitlana; Bolotnikova, Alla (Національний технічний університет "Харківський політехнічний інститут", 2026)
The process of developing a method for correcting the placement of the region of interest for a tracker has been investigated. The method is based on a nonlinear variable combination methodology that accounts for horizontal and vertical gradients. The justification for selecting the optimal method was carried out considering the number of operations per pixel and the computational complexity of the studied area. The accuracy criterion for region of interest placement correction was variance. To demonstrate the advantages of the proposed method, multiple video streams with varying frame counts were input into the tracker. A comparison was made with the well-known Channel and Spatial Reliability Tracker combined with a Kalman filter featuring different configurations. Results. A method for correcting region of interest placement using a nonlinear methodology requiring 8 operations per pixel has been developed. This method operates in conjunction with the tracker. In experimental videos, the variance decreased by an average of 10.25%, whereas existing methods showed deterioration ranging from -3.61% to -47.63%. The obtained results confirmed compliance with Technology Readiness Level 4. Scientific Novelty. The developed method for correcting the placement of the examined area in the object tracking task differs from existing ones by using combinations of nonlinear variables that take gradient analysis into account. This allows determining the displacement point of the region of interest based on horizontal and vertical gradients. Practical Significance. The proposed method can be used as an additional tool for real-time object tracking.

Процес підвищення ефективності супроводу об’єктів складних форм, що рухаються із лінійними та нелінійними траєкторіями. Методика. Досліджено процес розробки методу корекції розміщення регіону інтересу для трекери. В основу методу покладено методологію комбінацій нелінійних змінних, що враховують горизонтальні та вертикальні градієнти. Обґрунтування вибору оптимального методу здійснювалося із врахуванням кількості операцій на піксель та обчислювальної складності досліджуваної області. Критерієм точності корекції розміщення регіону інтересу була дисперсія. Для доведення переваг запропонованого методу використовувалося кілька відеопотоків із різною кількістю кадрів, які подавалися на вхід трекеру. Порівняння здійснювалося із відомим трекером Channel and Spatial Reliability Tracker у поєднанні з фільтром Калмана, що мав різні налаштування. Результати. Розроблено метод корекції розміщення регіону інтересу з використанням нелінійної методології, що має 8 операцій на піксель. Він використовується у взаємодії із трекером. На експериментальному відео дисперсія зменшилася у середньому на 10,25%, у той час як існуючі методи продемонстрували погіршення від -3.61% до -47.63%. Отримані результати підтвердили підтримку вимог Technology Readiness Level 4. Наукова новизна. Розроблений метод корекції розміщення досліджуваної області у задачі супроводу об’єктів відрізняється від існуючих використанням комбінацій нелінійних змінних із врахуванням аналізу градієнтів. Це дозволяє знаходити точку зсуву регіону інтересу на основі горизонтальних і вертикальних градієнтів. Практична значимість. Розроблений метод може бути використаний як додатковий інструмент супроводу об’єктів у онлайн режимі.
Розробка методу корекції розміщення регіону інтересу
Keywords: nonlinear variables; object tracking; placement correction; computer vision; artificial intelligence; нелінійні змінні; супровід об'єктів; корекція розміщення; комп'ютерний зір; штучний інтелект